(untitled) (Research, Society and Development, 2021)
Introduction: Diabetes Mellitus is a group of metabolic disorders that has as a characteristic an imbalance in the level of serum glucose. It is considered a major public health problem, due to its ability to develop into chronic and acute complications, and faces inadequate adherence to self-care, especially insulin therapy. Therefore, this study aimed to understand the contribution of the nursing consultation regarding psychosocial factors in the adherence to insulin therapy. Methodology: The research was guided by the Integrative Review method, carried out in the Virtual Health Library (VHL), in the following databases with on-line access: Nursing Database (BDENF), Latin American and Caribbean Literature on Health Sciences (LILACS) and MEDLINE. As well as, in PubMed Central (PMC) and SciElo Brazil, both through the CAPES Periodical Portal. Results and discussion: According to the literature surveyed, self-care was considered a factor of paramount importance in the success of the treatment of diabetic patients in general. Psychosocial aspects are related to the quality of adherence to insulin therapy and the nursing consultation is relevant in the process of building self-knowledge and a factor of adherence to self-care. Conclusion: The nursing consultation is an effective tool for adequate adherence to insulin therapy. However, planning done in agreement with the patient to meet their needs, should strengthen aspects of self-care protagonism and avoid situations of unnecessary dependence on the health team, which would affect the quality of life of the individual.